Modifikasi Relaksasi dengan Budaya Lokal untuk Menurunkan Kecemasan Atlet Pencak Silat Menghadapi Kejuaraan - Ari Khusumadewi; M. Ramli; Carolina Ligya Radjah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
This article aims to examine the effectiveness of modification of counseling strategies to reduce anxiety of pencak silat athletes against championship. The subjects in this study were pencak silat athletes. Pencak silat was chosen because this sport requires local culture in various aspects of life, namely wirasa, wiraga, and wirama. These three aspects develop and are applied to their behavior, feelings, and cognitive patterns. This study used a pretest-posttest kontrol design. The treatment given to the experimental group was a modification of the relaxation strategy. There were 10 research subjects in each group with random group determination. The pre-test mean of the experimental group was 74.70 and 78.20 in the kontrol group. Meanwhile, the mean post ice in the experimental group was 50.60 and 60.60 in the kontrol group. The data analysis technique used is the T-test. The results of the analysis of this study showed that the group that received a modification of the relaxation strategy with cultural elements had decreased anxiety levels more than the kontrol group. Culture influences the client's thinking, feeling, and behavior patterns. It’s mean that combining cultural elements with counseling strategies can effectively reduce athletic anxiety against championships.